KESALEHAN SOSIAL DALAM TASAWUF PRESPEKTIF ALQURAN - Suryan A Jamrah (Sosial Budaya, 2015)
Globally, the Qur'an has been much talk about science and technology, then to find out for sure we must have a faulty knowledge through comprehension and understanding of the universe and the nature and phenomenon. Science and technology is a field of activity that is continuously developed because it has a benefit as the life support manusia.Allah Subhaanahu Wa Ta'ala give sense to humans in order to make sense of this man has worked diligently to think seriously and deeply about all things and all events in the universe (universe) is both the method of induction and deduction that is achieved very nature the higher nature for then increased again so that people with minds that can recognize the highest truth that Allah Lord of the 'Alamin. Diciptaan universe Subhaanahu Allah Wa Ta'ala is a complete maha laboratory filled sign all Subhaanahu Mahaan Allah Wa Ta'ala for designing, creating, maintaining and later retrieve it. Detailed laboratory maha this will not work and will not be dynamic for human life if people do not want to contemplate and think to process them. Humans as diggers and seekers of knowledge is not enough just to read it without thinking. In the Qur'an, people are encouraged to use their minds and a lot of thinking